Phytochemical Screening and Antibacterial Activity Test Against Escherichia Coli Of Porang Leaf Extract ( Amorphophallus Muelleri) Blume) With Ethanol, Ethyl Acetate, And N-Hexane Extraction Solvents - Ni Made Dewini (Journal of Applied Psychology and Health Studies, 2025)
The common bacteria that causes diarrhea is Escherichia coli. Therapy for Escherichia coli bacterial infection uses antibiotics but the use of antibiotics that are relatively high can cause resistance, so alternative medicines are needed using herbal medicinal plants. Based on the studies, one of the plants that can be used as an antibacterial is the porang plant (Amorphophallus muelleri Blume) which is a type of plant that has potential both technologically and commercially in terms of medical, industrial and food. This study aims to determine the content of secondary metabolites and antibacterial activity contained in porang leaf extract (Amorphophallus muelleri Blume) with 96% ethanol, ethyl acetate and n-hexane as solvents. In the antibacterial activity test using the disc diffusion method with NA media (Nutrient Agar), ciprofloxacin as a positive control, 10% DMSO as a negative control and various concentrations of 15%, 30%, 45%, and 60%. The three porang leaf extracts can produce the greatest antibacterial activity at a concentration of 60%. Antibacterial activity in the ethanol extract of porang leaves had an average inhibition zone of 1.32 ± 0.59 mm, in the ethyl acetate extract of porang leaves it had an average inhibition zone of 0.73 ± 0.10 mm, and in the n-hexane extract of porang leaves it had an average resistance zone of 0.34 ± 0.39 mm. The results of this study concluded that the three porang leaf extracts with 3 solvents had antibacterial activity but the inhibition zone formed was in the weak category.